Arduino-Assisted Buoyancy Demonstration Tool for Physics Learning in High School - Putri, Feby Dwitri; Nasbey, Hadi; Indrasari, Widyaningrum; Samsudin, Achmad (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2025)
This study aims to produce a product in the form of a physics teaching aid for secondary school on the topic of Archimedes’ principle. The developed teaching aid consists of an Arduino as the main controller, a mass sensor to detect changes in the mass of the submerged object, and a beaker attached to acrylic and supported by a stand. The device can automatically record mass changes of the load and the measuring beaker. The research method employed is R&D with a 4D model, consisting of four stages: Define, Design, Develop, and Dessimination. The variable used is the variation in the depth of the submerged object. The Arduino output is presented in the form of data and graphs using Microsoft Excel. The product has undergone material and media validation tests with average percentages of 90.67% and 100%, respectively. Based on the results, it can be concluded that the Archimedes’ principle teaching aid using Arduino is valid as a supporting medium for physics learning. The limitation of this study is the absence of the dessimination stage involving teachers and students. However, this study successfully produced a teaching aid that can be used to support the physics learning process.